2001
DOI: 10.1097/00006123-200105000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Apolipoprotein E Genotype on Outcome after Spontaneous Subarachnoid Hemorrhage: A Preliminary Study

Abstract: There was underrepresentation of the epsilon4 allele in this group when compared with previously studied cases of subarachnoid hemorrhage with a fatal outcome and with the general population. This suggests that patients with the epsilon4 allele who have a subarachnoid hemorrhage are less likely to be admitted to a neurosurgical unit. This study does not support an association between possession of an epsilon4 allele and poor outcome in patients admitted to a neurosurgical unit with spontaneous subarachnoid hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 26 publications
3
23
1
Order By: Relevance
“…10,11,[35][36][37] Finally we included eight studies that investigated the prognostic role of the APOE genotype (total: 696 patients; 175 E4 carriers) or its effect on the occurrence of DI (total: 600 patients; 161 E4 carriers) (table 1). [5][6][7][8][9]12,13,38 All authors but one joined the collaborative group and contributed the requested data centrally.…”
Section: Resultsmentioning
confidence: 99%
“…10,11,[35][36][37] Finally we included eight studies that investigated the prognostic role of the APOE genotype (total: 696 patients; 175 E4 carriers) or its effect on the occurrence of DI (total: 600 patients; 161 E4 carriers) (table 1). [5][6][7][8][9]12,13,38 All authors but one joined the collaborative group and contributed the requested data centrally.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the TNF-A 308 G/A polymorphism was found to be associated with outcome after cerebral infarction [15]. Heterogeneous results have been found in previous studies on the APOE ε4 genotype and outcome after aneurysmal SAH: two studies found that the APOE ε4 allele is related to poor outcome [28,32] while a third study did not find an association [10]. Possible differences in these findings may be attributable to the small patient groups studied (approximately 100 [28,32]), to differences in adjustment Genotyping data were available for 167 patients for the APOE, IL-1A and TNF-A polymorphisms, for 165 patients for the IGF-1 and IL-6 polymorphisms, and for 164 patients for the IL-1B polymorphism * WT/non-WT = ε3/4 or ε2/4; ** WT/non-WT = ε2/3 APOE ε2/ε3/ε4 apolipoprotein ε2/ε3/ε4 allele; WT wild type allele; non-WT non-wild type allele; IGF-1 insulinlike growth factor-1; TNF-A tumor necrosis factor-A; IL-1A interleukin-1A; IL-1B interleukin-1B; IL-6 interleukin-6 for prognostic factors (e. g. no adjustment for rebleeds [10,28] or secondary cerebral ischaemia 10, 28, 32]), or to inclusion of patients with non-aneurysmal SAH [10].…”
Section: Discussionmentioning
confidence: 99%
“…29 The authors found no correlations but the phenotype mix and the consequent heterogeneity-related increase in the covariates increased the risk of false-negative conclusions in the context of an underpowered study with limited potential for adjusting for confounding factors.…”
Section: Original Case Series: Functional Outcomementioning
confidence: 96%